Case report: Malignant melanoma of the lower limb with gastric metastasis - Hu, Qiang; Zhou, Fengru; Sun, Yuanshui (Frontiers in Oncology, 2023)
Introduction: Malignant melanoma with gastric metastasis is extremely rare. We report a case of gastric metastasis caused by malignant melanoma of the lower limbs . Case Presentation: A 60-year-old female was hospitalized for left plantar pain . The patient found that there was a black maculopapular eruption on the left sole of her left foot, which caused pain when pressing and aggravated by walking, so she went to our hospital for treatment. On the second day of admission, the lesion of the left foot was removed under local anesthesia, and the removed tissue was sent for pathological examination. Combined with immunohistochemistry, it was consistent with malignant melanoma. During hospitalization, the patient developed abdominal pain and asked for gastroscopy. Gastroscopy revealed two 0.5 cm× 0.6 cm spots can be seen arising from the stomach mucosa was slightly swollen, slightly black in the center, without erosion and no abnormality was found in other parts. At the same time, biopsy was taken under gastroscope and pathology suggests malignant melanoma. The patient could not undergo subsequent treatment due to the cost. The patient was followed up to February 2022 and was within the survival period. Conclusion: Malignant melanoma gastric metastasis is extremely rare. When a patient has a previous history of melanoma surgery, it needs to be considered when presenting with gastrointestinal symptoms, and regular endoscopic screening. Early surgical treatment and postoperative chemotherapy or combined targeted therapy may improve the prognosis of patients.